CURRENT ISSUES OF INTERNATIONAL COOPERATION OF THE REPUBLIC OF KAZAKHSTAN IN THE FIELD OF CIVIL LEGAL TRAFFIC INFORMATION - Abdrassulova , Гульнар Эркеблановна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
This article discusses the current problems of a multidimensional topic of international cooperation in the field of civil-law circulation of information as the most important condition for Kazakhstan’s participation in global information processes. Our state will have to change significantly in order to be able to meet the high standards and principles set by the international community on this side of society’s activities. Our state will have to change significantly in order to be able to meet the high standards and principles set by the international community on this side of society’s activities. The increasingly active integration of the Republic of Kazakhstan into the international economic and information space requires the improvement of legal and technological protection mechanisms, effective interaction of stakeholders on the protection of intellectual property objects at border crossings, judicial protection in the field of copyright and related rights, industrial property and other vital values. In Kazakhstan, the modern process of improving the legal regulation of relations related to rights to information is related to solving a whole range of tasks, including those related to overcoming gaps and conflicts in legislation governing relations in the area of ​​rights to information and related intellectual property, developing an effective mechanism judicial protection of these rights. Their early resolution, ultimately, is aimed at forming an effective system that allows regulating civil-legal circulation of information by the most civilized methods meeting the high requirements of international standards. The author of the article explores certain topical problems of international cooperation of the Republic of Kazakhstan in the field of civil-law circulation of information, and also makes his own proposals for improving this process.